MENINGKATAN AKTIVITAS DAN HASIL BELAJAR SISWA MENGGUNAKAN METODE PRAKTIKUM - Khumairo, Siti Nurafni; Sahputra, Rachmat; Hadi, Lukman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe aimof this study is to improve activity and achievement of students of Madrasah Aliah (MA) Alhabib Sholeh convey electrolyte solution and non electrolyte through experiment method. To this, observation and achievement test used as data collection tools. The participants of this study were 26 students of X B class. The instruments used in this research were the observation sheet and learning achievement test.The results showed that the application of the assignment methods can increase the percentage of students with learning activities of 30,76% in cycle 1 becomes 57,69% in cycle II. The results of the study showed an increase in the percentage of students from 34,61% in cycle 1 becomes 69,23% in cycle II. The increase in activities that occur from cycle 1 to cycle II of 26,93% and improved learning achivement that occur from cycle 1 to cycle II of 34,62%. In conclusion, experiment method is able to improve activity and achievement of students. Keywords: learning activities, practical methods, and the results of the study.